Analisis Structural Assurance dan Perceived Reputation terhadap Sistem Informasi Akuntansi yang dimoderasi oleh Trust - Rachma Widyani; Ajeng Wijayanti (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
The purpose of this study is to recommend influence structural assurance and perceived reputation to accounting information systems and testing the effect of moderation of trust on structural assurance and perceived reputation towards accounting information systems. The research method used is quantitative with data collection techniques through questionnaires, the number of samples obtained was 289 respondents with the population of MSMEs in DKI Jakarta. The data processing method in this study uses software smart PLS used for validity testing and reliability testing and hypothesis testing. From the test results the hypothesis proves that there is a significant effect of structural assurance to accounting information systems, there is a significant influence of perceived reputation towards accounting information systems, the absence of a significant influence of trust in accounting information systems, the absence of a significant influence of moderation of trust over structural assurance , and the absence of a significant influence of moderation of trust in perceived reputation .